2012
DOI: 10.1002/stem.1242
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of the MHC‐I and Its Regulation by NFκB in Human‐Induced Pluripotent Stem Cells

Abstract: The immunogenicity of human pluripotent stem cells plays a major role in their potential use in the clinic. We show that, during their reprogramming, human-induced pluripotent stem (iPS) cells downregulate expression of human leukocyte antigen (HLA)-A/B/C and b2 microglobulin (b2M), the two components of major histocompatibility complex-I (MHC-I). MHC-I expression in iPS cells can be restored by differentiation or treatment with interferongamma (IFNc). To analyze the molecular mechanisms that regulate the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
(58 reference statements)
4
16
0
Order By: Relevance
“…Recent research indicated a significant positive correlation between MHC-I and the nuclear factors, NFκB1 and RelA, pointing to the critical role of NFκB proteins in regulating the MHC-I expression in human iPS cells [34]. In their study, Pick and colleagues reported that over-expression of NFκB1 and RelA in undifferentiated iPS cells could lead to induction of MHC-I expression and silencing of NFκB1 and RelA by shRNA results in decreased expression of β-2M after IFN-γ treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent research indicated a significant positive correlation between MHC-I and the nuclear factors, NFκB1 and RelA, pointing to the critical role of NFκB proteins in regulating the MHC-I expression in human iPS cells [34]. In their study, Pick and colleagues reported that over-expression of NFκB1 and RelA in undifferentiated iPS cells could lead to induction of MHC-I expression and silencing of NFκB1 and RelA by shRNA results in decreased expression of β-2M after IFN-γ treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is entirely possible that this immunogenicity could further increase during differentiation to specific tissues, as has been observed during differentiation of ES cells with increasing expression of HLA [30][33]. A recent study has demonstrated that upregulated expression of NFκB1 and RelA, two members of NFκB family during cell reprogramming, could increase the expression of HLA-I in iPS cells [34]. Suárez -Alvarez et al have shown that revealed HLA-B and β-2M can activate the transporter associated with antigen processing and can thus increase immunogenicity through induction of H3K4me3 modification during the differentiation [35].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…To circumvent this, commonly available iPSCs from healthy donors may be used for comparison. MRC5-derived (fetal lung fibroblast) iPSCs have been utilized as a control in several previous reports, 13,[37][38][39][40][41] and can be obtained from the public bank. If MRC5-iPSCs do not demonstrate pathogenic phenotypes that disease iPSCs do under the same experimental condition, MRC5-iPSCs would serve as a practical control.…”
Section: Quest For Suitable Controls Of Disease Ipscsmentioning
confidence: 99%